Responsive Envelopes: Experimentations by natural Role Models - Ingrid Paoletti Paoletti (Agathón)
This paper aims at investigating the possibility to design responsive envelopes starting from the role models of nature. Nature adopts very interesting role models depending on external stimuli and in relation to its own form. For example, the tactical, tropical and nastic movements respond to stimuli like humidity, sun and heat. In Architecture, the ability to develop responsive envelopes arises from the need to modulate the performance of the first filter between inside and outside with dynamic solutions that can be activated depending on people, climatic changes or the presence of particular conditions. The ability to modulate performance goes in the direction of more and more sustainable solutions that can reduce the amount of material and at the same time adapt to the environmental context in which they are positioned. Studying nature models can develop innovative technical solutions while expanding the designer’s know-how, thanks to computational design techniques, which help to mathematically inform the design of solutions and simulate their behaviour. An experimental prototype carried out at the ABC Department of the Polytechnic of Milano University, ACTLAB Research Unit, will show the realization of a responsive pneumatic envelope studied from the models of nature and produced either with additive and forming techniques.